2015
DOI: 10.1039/c4sm02334j
|View full text |Cite
|
Sign up to set email alerts
|

Rounding of the localization transition in model porous media

Abstract: The generic mechanisms of anomalous transport in porous media are investigated by computer simulations of two-dimensional model systems. In order to bridge the gap between the strongly idealized Lorentz model and realistic models of porous media, two models of increasing complexity are considered: a cherry-pit model with hard-core correlations as well as a soft-potential model. An ideal gas of tracer particles inserted into these structures is found to exhibit anomalous transport which extends up to several de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 56 publications
1
45
0
Order By: Relevance
“…Above a critical obstacle density, the test particle can no longer explore the whole environment but stays trapped and long-range transport is effectively suppressed. Höfling et al have observed that in two dimensions and close to the critical density diffusive and ballistic particles show the same subdiffusive motion in a random Lorentz gas [44,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Above a critical obstacle density, the test particle can no longer explore the whole environment but stays trapped and long-range transport is effectively suppressed. Höfling et al have observed that in two dimensions and close to the critical density diffusive and ballistic particles show the same subdiffusive motion in a random Lorentz gas [44,[47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…η = 0. Upon increasing the packing fraction the critical obstacle density decreases, and as a peculiarity in 2D systems a minimum emerges at η ≈ 0.5 and increases again for even higher packing fractions [76]. This feature is not present in the corresponding 3D analog [55].…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 76%
“…An equilibrated sample is quenched and acts as host structure for soft noninteracting tracer particles, see Figure 4. The first observation is that for an ideal gas of tracers in the canonical ensemble the localization transition is replaced by a rapid but smooth crossover [76]. This can be easily rationalized since for soft interactions the barriers introduced by the host structures are finite, therefore the question if a tracer meanders through the entire system or not is strongly energy-dependent.…”
Section: The European Physical Journal Special Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boolean Models are well established models for porous materials from stochastic geometry [39][40][41]. There, porous structures are composed of overlapping grains with random position and orientation (i.e., points in a plane are chosen randomly in a Poisson point process).…”
Section: Boolean Modelsmentioning
confidence: 99%